Solid waste and septage co-composting as a pathway to cost and resource recovery in Sri Lanka - Fernando, Sudarshana; Drechsel, Pay; Jayathilake, Nilanthi; Semasinghe, Christina (2014)
Due to its low nutrient content, compost from municipal solid waste (MS\I\1 qualifies mostly as a conditioner of soil physical properties than soil fertility. This limits the value proposition of the compost and its potential for cost recovery to maintain the compost stations. One way to enhance the compost value is to enrich it with nutrients. Given the increasing attention to fecal sludge (FS) management from septic tanks and latrines, co-composting of both waste streams could be a win-win option to increase the compost nutrient value. To assess the current situation of MSW composting and opportunities and acceptance of co-composting in Sri Lanka several field surveys were conducted including a study of 13 MSW compost plants and current septage management practices in 41 local authorities (LA), a detailed case study of an existing plant mixing MSW and FS, and a willingness to pay study among 257 farmers in proximity of a designated pilot co-composting station. The average cost recovery percentage of the existing compost plants was less than one third of the O&M costs in Sri Lanka with significant variations. The willingness to pay study indicated a high interest in enriched compost. Field trials showed that co-composting with septage could enhance the MSW compost nutrient value. For example, the Phosphorous content of 0.4% could be increased nearly 10 times. In general, co-composting could increase the financial sustainability of the existing compost plants to a substantial degree, while nutrient recovery from MSW without septage addition may not be financially sustainable. Pelletized co-compost could have an increased market value of 70%-1000,1, compare to the normal MSW compost.